PENGARUH TINGKAT SUKU BUNGA BANK INDONESIA, KUPON OBLIGASI, WAKTU JATUH TEMPO OBLIGASI, DAN NET PROFIT MARGIN (NPM) EMITEN TERHADAP HARGA OBLIGASI YANG TERDAFTAR DI IBPA TAHUN 2012 – 2016 - Firman Ferdian; Hari Gursida; Arief Tri Hardiyanto (Universitas Pakuan, 2021)
The purpose of this research is to examine the influence BI rate, maturity, coupon bond, and net profit margin (NPM) emiten to bond prices which are listed in Indonesia Bond Price Agency (IBPA). The population has been obtained by using purposive sampling on emisi which are listed in Indonesia Bond Price Agency in 2012 - 2016 periods and based on the predetermined criteria 49 emisi have been selected as samples. The analysis method has been done by using multiple linear regression analysis and the SPSS (Statistical Product And Service Solutions) 23. The result of partial test shows that (1) BI rate, and coupon bond give influence to the bond price. (2) There is influence between BI rate (X1) , coupon bond (X2), maturity (X3), and Net Profit Margin (NPM) Emiten (X4) together with bond prices.